Pisinisi laititi : Samoan women and the informal sector : a thesis presented in fulfilment of the requirement for the degree of Master of Philosophy in Development Studies at Massey University - Dunlop, Emma Repeka (Massey University, 1999)
The informal sector has become an important concept in development theory and practice since its introduction in the early 1970s. The informal sector is the term given to the small economic activities, which involve labour-intensive methods of production and labour. These activities are considered 'informal' because they generally operate outside the legal environment, and therefore largely escape recognition, enumeration, regulation and protection by the Government. Research on the informal sector in the Pacific proposes that informal sector activities are the major means of livelihood security for a significant number of Pacific families today. Further it is unlikely that Pacific Countries will be able to create sufficient paid employment opportunities to meet the growing demands for waged jobs. To date there has been very little research on Samoa's informal sector activities or the role of the informal sector within the macro-economy. This general lack of recognition of informal sector activities reflects that these activities are traditionally seen as 'women's work' - a way in which women earn 'pin money' to supplement the family budget. Recognition of women's work is a key strategy in women's empowerment - an approach that has become very closely aligned with poverty alleviation strategies in the world. This is a study of Samoan women and the informal sector. This research has two aims: the first is to review the nature and extent of Samoan women's informal sector activities today, and to review the adequacy and effectiveness of the measures in place to support women's activities. Based on these findings, the second aim of this research is to examine the extent to which macro-level recognition and research of the role of the informal sector in the Samoan economy, should be encouraged. Samoan women are the sample group, because women are a very visible part of the informal sector scene today. The results of the fieldwork show the importance of the informal sector to individual empowerment, household social and economic security, community development and the national economy. Samoan women are predominantly involved in agricultural and agricultural-related activities, thus reinforcing the semi-subsistence economy. Samoan women are also involved in 'multiple economic activities' - a strategy which is used to spread risk over a number of options. The study also found that the money that Samoan women earn in their informal sector activities is vital to the livelihood security of their families. This research concludes with a discussion of the ways in which the informal sector in Samoa can be encouraged and developed.
Keywords: Women in development; Informal sector (economics); Economic conditions; Samoa